2011
DOI: 10.1016/j.ejvs.2011.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Clinical Variables and Gene-expression Profiles in Carotid Plaque Instability

Abstract: Here, we demonstrate that gene-expression profiles reflect clinical parameters. Our results suggest that microarray technology and clinical variables can be used for the future identification of central molecular pathways in plaque instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 26 publications
3
37
1
2
Order By: Relevance
“…Pelisek et al also reported increased serum MMP-1 and MMP-7 levels in 64 patients with histological unstable atherosclerotic carotid lesions [7]. By using a microarray approach, Razuvaev et al examined mRNA levels in 106 carotid plaques, and showed that high expression of MMP-7 and MMP-9 was associated with an unstable plaque phenotype [18]. In the present study we extend these previous findings by showing increased MMP-7 levels systemically as well as within the atherosclerotic lesion in patients with carotid atherosclerosis with the most recent symptoms (i.e., within two months).…”
Section: Discussionmentioning
confidence: 99%
“…Pelisek et al also reported increased serum MMP-1 and MMP-7 levels in 64 patients with histological unstable atherosclerotic carotid lesions [7]. By using a microarray approach, Razuvaev et al examined mRNA levels in 106 carotid plaques, and showed that high expression of MMP-7 and MMP-9 was associated with an unstable plaque phenotype [18]. In the present study we extend these previous findings by showing increased MMP-7 levels systemically as well as within the atherosclerotic lesion in patients with carotid atherosclerosis with the most recent symptoms (i.e., within two months).…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] Microarray data from plaque tissue in the Biobank of Karolinska Endarterectomies (BiKE) cohort, available for n=125 patients, were analyzed for association with rs17293632C>T. Because neither this SNP nor rs56062135C>T were present on the chip, rs16950687A>G (D′ 0.949; r 2 0.859 with rs17293632; D′ 1; r 2 0.953 with rs56062135) was used as a proxy SNP. As shown, rs16950687A>G was significantly associated with SMAD3 mRNA levels in carotid lesions (P<0.05; Figure 3B).…”
Section: Turner Et Al Functional Analysis Of the Smad3 Locus For Cad 977mentioning
confidence: 99%
“…MMP-7 has been reported to be increased by over 100-fold in patients with atherosclerotic carotid plaques and associated with plaque instability (82). In addition the upregulation of MMP-7 correlated with overexpression of inflammatory genes, RANKL and CD68 (82).…”
Section: Types Of Mmps and Their Involvement In Diseasesmentioning
confidence: 99%
“…MMP-7 has been reported to be increased by over 100-fold in patients with atherosclerotic carotid plaques and associated with plaque instability (82). In addition the upregulation of MMP-7 correlated with overexpression of inflammatory genes, RANKL and CD68 (82). In spontaneously hypertensive rats, the increase in MMP-7,-9 and elastase expressions has been demonstrated to cleave ICAM-1 in the glomeruli leading to renal inflammation (83).…”
Section: Types Of Mmps and Their Involvement In Diseasesmentioning
confidence: 99%